Consumption Taxes: Consumed Income, National Sales, and the V.A.T. (Tufts Archival Research Center, 2007)
Memo from Tobacco Institute economist E J Battison to Fred Panzer regarding consumption taxes. Compares consumed income tax, national sales tax, and value added tax in terms of their federal and personal effect, especially relating to the low income bracket. Asserts that consumption tax would be effective, national sales tax has both pros and cons, and a value added tax is dangerous.